Role of Flutamide on Testosterone Induced Prostatic Hyperplasia in Long Evans Rats (Bangladesh Journal of Anatomy, 2010)
Context: Testosterone is the male sex hormone responsible for growth of secondary sexual character and accessory sex organs. Despite the effectiveness as a male sex hormone, testosterone causes Benign Prostatic Hyperplasia (BPH) resulting in urinary dysfunction. On the other hand, flutamide is a pure antitestosterone, which blocks the effects of Dihydro testosterone (DHT) at the testosterone receptor and prevents BPH. Therefore the present study was designed to observe the protective role of flutamide on testosterone induced prostatic hyperplasia. Objective: To observe the effects of flutamide on testosterone induced prostatic hyperplasia in Long Evans rats. Study design: An experimental study. Place and period of study: The study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka during the period of July 2006 to June 2007. Materials & Methods: Forty five matured male long Evans rats of age 8-10 weeks and weighing 200-300 gms were used in this study. They were divided into three equal groups. Group A was vehicle (olive oil) control group, Group B was testosterone treated group and Group C was testosterone & flutamide treated group. Comparative study in different groups were done microscopically. Results: There was significant reduction (P